Error Analysis in Pronouncing English Words Containing Diphthong Sounds Made by EFL Students - Suciati, Tia; Kurniawan, Ildi; Elfrida, Elfrida (Journal of English Education and Teaching, 2024)
This research aims to find out the ability in pronouncing diphthong sounds /ai/, /ei/and /oi/ the English Department Students of the English Education Study Program at the University of Bengkulu. This research was descriptive quantitative analysis. The population was the fourth-semester students' English study program, University of Bengkulu. The sample was selected by Random Sampling, totalling 38 students who were taken randomly from each class. The data were collected by several pronunciation tests with English words which contain English diphthongs /ai/, /ei/, /oi/. Data collection was supported by audio recording. The data obtained was then analyzed using the Audacity application with the help of Google Translate as a reference for the pronunciation received. The result of this study showed that most English students’ pronunciation of the word diphthongs was bad pronunciation; the three diphthongs got more than half of the students' mispronunciations. In conclusion, the ability in pronouncing the diphthong sounds /ai/, /ei/ , and /oi/ was poor and the dominant respondent's pronunciation error was diphthong /oi/. For future researchers, it is recommended to continue this research by investigating the problems of English students from all types of English diphthongs with a larger sample and investigating the causal factors.